Estimation of outcrossing rates in acerola (Malpighia emarginata) based on isoenzymic data - Lopes, Ricardo; Bruckner, Cláudio Horst; Lopes, Maria Teresa Gomes (Pesquisa Agropecuaria Brasileira, 2002)
Acerola (Malpighia emarginata) is a species of Malpighiaceae family that produces fruits with high vitamin C content. The increasing demand for acerola and its derived products caused the search for improved varieties to expansion of commercial plantation. The objective of this work was to gain information about a breeding system from an acerola population located in Visconde do Rio Branco, MG, Brazil. Ten families originating from seeds of a natural pollination were used. Plants were assayed for seven isoenzymatic loci (Idh, Mdh-1, Mdh-2, Pgm-1, Pgm-2, Est-1 and Pod) and the data were analyzed using a mixed mating model. Multilocos outcrossing rate estimate for population did not differ statistically from 1.00, whereas estimates ranged from 0.68 to 1.00 between families, and two estimates were significantly different from 1.00. Acerola is predominately allogamous and outcrossing rate varied between families; this fact should be taken into consideration in further breeding programs and germoplasm conservation.